PD-L1 Up-Regulation in Prostate Cancer Cells by Porphyromonas gingivalis - Groeger, Sabine; Wu, Fan; Wagenlehner, Florian; Dansranjav, Temuujin; Ruf, Sabine; Denter, Fabian; Meyle, Joerg (Frontiers in Cellular and Infection Microbiology, 2022)
Chronic inflammation is known to contribute to various human cancers. Porphyromonas gingivalis (P. gingivalis), is a gram-negative oral keystone pathogen that may cause severe periodontitis and expresses several virulence factors to affect the host immune system. Periodontitis is a chronic infectious disease that while progression, may cause loss of attachment and destruction of the tooth supporting tissues. Prostate cancer is one of the most common malignancies in men. Increasing evidence links periodontitis with prostate cancer, however the mechanisms explaining this relationship remain unclear. The aim of this study was to investigate the expression and signaling pathway of programmed death ligand 1 (PD-L1) in a prostate cancer cell line after infection with P. gingivalis and stimulation with P. gingivalis components to reveal the mechanism of tumor-induced immune evasion associated with bacterial infection in the tumor environment. Prostate cancer cells were infected with different concentrations of viable P. gingivalis and treated with different concentrations of heat-killed P. gingivalis and P. gingivalis cell components, including the total membrane fraction, inner membrane fraction, outer membrane fraction, cytosolic fraction and peptidoglycan (PGN). Chemical inhibitors were used to block different important molecules of signaling pathways to assess the participating signal transduction mechanisms. PD-L1 expression was detected by Western blot after 24 h of infection. PD-L1 was demonstrated to be upregulated in prostate cancer cells after infection with viable and with heat-killed P. gingivalis membrane fractions. Also isolated PGN induced PD-L1 up-regulation. The upregulation was mediated by the NOD1/NOD2 signaling pathway. No upregulation could be detected after treatment of the cells with P. gingivalis lipopolysaccharide (LPS). These results indicate, that chronic inflammatory disease can contribute to tumor immune evasion by modifying the tumor microenvironment. Thus, chronic infection possibly plays an essential role in the immune response and may promote the development and progression of prostate cancer.